Implementasi Asimetris Kuantum dalam Kriptografi Modern untuk Enkripsi Data Satu Arah - Raihan Muzafi; Arif Abdillah; Ainul Marziah; Shaffanisa Aulia Rizky; Abdi Prizayanto; Aisyah Nurhiqmah (JIKUM: Jurnal Ilmu Komputer, 2025)
In a company, data security is very important. Data security and integrity issues must be considered to prevent information from falling into the hands of unauthorized persons. Therefore, a good mechanism is needed to secure data, which can be done through various cryptographic methods, which are generally divided into two categories: symmetric and asymmetric. Currently, the development of quantum computing shows extraordinary potential, especially in the field of cryptography. The phenomenon of quantum supremacy, where quantum computers can solve problems that cannot be solved by classical computers, is increasingly being felt. This raises uncertainty in the existing data security system, because various cryptographic algorithms and protocols are predicted to be quickly solved by sufficiently powerful quantum computers. To overcome this potential insecurity, the field of cryptography must adapt, one of which is through the concept of quantum key distribution which offers a new standard in secure communication. In symmetric key cryptography, a secure communication channel is required for key delivery, and the concept of quantum key distribution is a promising alternative to overcome this problem. This study aims to explore the implementation of quantum asymmetric cryptography in one-way data encryption, as well as assess its effectiveness in improving information security.